2011
DOI: 10.2147/ppa.s24518
|View full text |Cite
|
Sign up to set email alerts
|

Obedience and motivation as mechanisms for adherence to medication: a study in obese type 2 diabetic patients

Abstract: ObjectiveTo clarify the mechanisms of adherence.MethodsA cross-sectional, multicenter French study using a self-questionnaire administered by 116 general practitioners to 782 obese type 2 diabetic patients.ResultsThe analysis of 670 completed questionnaires revealed a strong association between the adherence to medication and the behavior of fastening the seatbelt when seated in the rear of a car. Multivariate analysis indicated that this behavior was an independent determinant of adherence to medication (odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
5
18
0
4
Order By: Relevance
“…This study confirms the known determinants of adherence observed in the multivariable analysis, ie, older age,3437 abstinence from drinking,38 metabolic control,30,31,39 and the presence of complications 37. Surprisingly, we did not observe any association between nonsmoking and adherence, which was shown in some studies 4043.…”
Section: Discussionsupporting
confidence: 90%
“…This study confirms the known determinants of adherence observed in the multivariable analysis, ie, older age,3437 abstinence from drinking,38 metabolic control,30,31,39 and the presence of complications 37. Surprisingly, we did not observe any association between nonsmoking and adherence, which was shown in some studies 4043.…”
Section: Discussionsupporting
confidence: 90%
“…Les recommandations actuelles sur la prise en charge de l'HTA soulignent l'importance de renforcer le mode de vie et l'observance thérapeutique [14,15] même s'il n'existe pas de moyen simple pour y arriver [16]. La motivation est déjà connue comme étant un facteur clé de l'observance médicamenteuse des patients diabétiques obèses [11]. Évaluer le niveau de motivation devrait donc être la première action à mener chez un patient hypertendu non contrôlé.…”
Section: Discussionunclassified
“…Ce document comportait l'AQ du Comité français de lutte contre l'HTA qui permet d'estimer l'observance [9,10], des éléments sur la motivation du patient à suivre les recommandations du médecin [11] et sur la situation de précarité du patient [12]. La perception du patient sur l'HTA et le nombre de comprimés quotidiens pour l'HTA et pour d'autres pathologies ont aussi été recueillis.…”
Section: Données De L'auto-questionnaireunclassified
“…Paradoxically, the absence of knowledge can potentially help adherence in that passive followers (those that do as the doctor tells them to do) may adhere better to medication. One study suggested that some patients adhere to medications simply because they generally follow rules (the study compared this to wearing a seat belt in the rear of the car [22]), or perhaps patients have trust in their doctor and medical plan [16]. On the contrary, patients without complete knowledge may have decreased adherence due to this lack of knowledge, along with personal beliefs that may conflict with management.…”
Section: Natural Remedies Well After Um [-] Probably a Year And A Halmentioning
confidence: 99%